2021
DOI: 10.1039/d1cc02958d
|View full text |Cite
|
Sign up to set email alerts
|

Insights into carbon nanotube-assisted electro-oxidation of polycyclic aromatic hydrocarbons for mediated bioelectrocatalysis

Abstract: A series of polycyclic aromatics, naphthalene, phenanthrene, perylene, pyrene, 1-pyrenebutyric acid N-hydroxysuccinimide ester (pyrene NHS) and coronene, were immobilized via π stacking on carbon nanotube (CNT) electrodes and electro-oxidized in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The detection of two oxidation peaks due to the formation of cation-radicals from the electrochemical oxidation of pyrene has been observed in a previous work [75]. Also, the two isomers; 1, 6-pyrenedione and 1, 8-pyrenedione were reportedly formed during the electrochemical oxidation of pyrene in previous studies [76]. A single irreversible oxidation peak was observed on the GCE/fMWCNTs which could be as a result of the compression of the potential difference between the two waves, merging to produce one voltammetric wave as Scheme 1.…”
Section: The Electrocatalytic Response Of the Electrodes To Pyrene Ox...mentioning
confidence: 53%
“…The detection of two oxidation peaks due to the formation of cation-radicals from the electrochemical oxidation of pyrene has been observed in a previous work [75]. Also, the two isomers; 1, 6-pyrenedione and 1, 8-pyrenedione were reportedly formed during the electrochemical oxidation of pyrene in previous studies [76]. A single irreversible oxidation peak was observed on the GCE/fMWCNTs which could be as a result of the compression of the potential difference between the two waves, merging to produce one voltammetric wave as Scheme 1.…”
Section: The Electrocatalytic Response Of the Electrodes To Pyrene Ox...mentioning
confidence: 53%
“…This oxidation is aimed at generating the phenanthrolinequinone derivative at the surface of MWCNTs. 37,38 The electrodes are cycled 30 times in phosphate buffer at pH 7.0 from −0.4 V to +1.2 V vs. SCE (saturated calomel reference electrode) at 100 mV s −1 . The generation of the phenanthrolinequinone is conrmed by the appearance of a reversible redox system at E 1/2 = −0.12 V vs. SCE, corresponding to the 2e − /2H + oxidation of the quinone derivative.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, thionine-modied gold nanoparticles on CNTs exhibit maximum catalytic currents of 1.6 and 3.7 mA cm −2 for glucose oxidation by adsorbed FAD-GDH at similar overpotential. 37,38 FAD-GDH coadsorbed with phenanthrolinequinone exhibits a maximum current density of 5.4 mA cm −2 at homemade CNT-based composite bucky-paper electrodes. 39 Electrosynthetized pyrenedione, co-adsorbed with FAD-GDH showed a maximum current density of 7.5 mA cm −2 (onset potential = −0.14 V) 37,38 while phenanthrolinequinone-based Ru(II) complexes bearing pyrene groups show a maximum current density of 1.4 mA cm −2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A and B). 85 Holzinger et al 88 non-covalently functionalized CNT with a series of polycyclic aromatics via π–π interactions and systematically investigated their electro-oxidation properties. Their results demonstrated that the formed pyrenedione is appropriate for mediated electron transfer of FAD dependent glucose dehydrogenases with excellent bioelectrocatalytic activity and stability for the oxidation of glucose.…”
Section: Surface Functionalizationmentioning
confidence: 99%